REKONSTRUKSI KONSEP KHALIFAH DALAM AL-QUR’AN DAN MODEL ETIKA KONSERVASI LINGKUNGAN - Reski; Majid, Abdul; Fuad Fansuri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The environmental crisis is not merely a technical problem but also reflects a crisis in the way humans understand their position toward nature. This study reconstructs the Qur’anic concept of khalīfah and formulates its relevance to environmental conservation through a systematic ethical model. It is qualitative library research employing thematic exegesis (tafsīr mauḍū‘ī). Primary sources comprise the Qur’an—especially Q. 2:30 and Q. 38:26—verses containing khalīfah and its derivatives, and selected classical and contemporary commentaries. Data were collected through documentation and analyzed descriptively and analytically by inventorying verses, classifying their functions, examining linguistic meanings, comparing interpretations, synthesizing thematic findings, and relating them to Qur’anic ecological values. The study identifies nine dimensions of khalīfah: divine appointment, succession and intergenerational continuity, human trusteeship on earth, general and specific dimensions of authority, truth and justice as guidance, self-restraint, status as a test, the capacity to improve or destroy, and accountability. These dimensions are thematically connected with amānah, mīzān, the prohibition of fasād, responsible development of the earth, iṣlāḥ, and the prohibition of isrāf. The connection yields six conservation principles and a normative-conceptual ethics model with theological, ethical, and ecological foundations. Its seven operational stages are recognizing trust, assessing impacts, limiting utilization, protecting environmental functions, preventing damage, restoring damage, and accounting for actions. The findings position environmental conservation as a concrete expression of human vicegerency rather than an optional moral concern.